Integrating China into multilateral debt relief: Progress and problems in the G20 DSSI - Deborah A. Bräutigam; Yufan Huang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2023)
On March 25, 2020, as the COVID-19 pandemic swept across the world, the heads of the International Monetary Fund (IMF) and the World Bank proposed that the leaders of the world's 20 largest economies, the Group of 20 (G20), provide breathing space by suspending the collection of debt service on official loans to 73 of the world's poorest countries. The G20 quickly launched the Debt Service Suspension Initiative (DSSI) on April 15, 2020. The DSSI was the first big test of the G20's global economic coordination leadership regarding low and middle-income country sovereign debt. The changing pattern of global credit demanded a new architecture for solving debt crises. Since 2008, the G20 has been the premier forum for international economic coordination, but the G20 had not previously worked with the Paris Club. The DSSI was intended by some of its designers to bring China into a well-oiled system for global sovereign debt governance, with the Common Framework as the scaffold upon which a new architecture would be built. Through analysis of available data, process-tracing through over 100 interviews with G20 participants and borrowers, and case studies, we argue, with some caveats, that China fulfilled its role fairly well as a responsible G20 stakeholder implementing the DSSI.
Keywords: 330